Anti-pollution flashover coating with arc durability and preparation method thereof

Through the ceramicization of modified mica powder, glass powder and calcium carbonate and the addition of potassium titanate whiskers, a dense ceramicized layer is formed, which solves the problem of poor arc resistance performance of existing antifouling flash coatings under high pressure conditions, and realizes the Efficient arc durability and mechanical performance improvements.

CN119119864APending Publication Date: 2024-12-13BEIJING CHENGZHU ZHIYAN ELECTRIC POWER TECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202411326755.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing antifouling flash coatings are difficult to meet the application requirements of DC ultra-high voltage transmission networks above 1000kV under high pressure conditions, and the large addition of fillers such as aluminum hydroxide affects the mechanical properties and surface hydrophobicity of the coating. Traditional arc-resistant agents are at high temperatures. Poor durability.

Method used

Modified mica powder, modified glass powder and modified calcium carbonate of specific particle size and grade, combined with potassium titanate whiskers, mica powder and glass through 1,2-bis(trimethoxysilyl)ethane The powder and calcium carbonate are modified to form a dense ceramic layer to improve the arc resistance of the coating.

Benefits of technology

It significantly improves the arc durability and mechanical properties of the coating, meets the requirements of trace resistance and corrosion resistance in high-voltage environments, and complies with the power industry standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005055616810000081
    Figure BDA0005055616810000081
  • Figure BDA0005055616810000091
    Figure BDA0005055616810000091
  • Figure BDA0005055616810000111
    Figure BDA0005055616810000111
Patent Text Reader

Abstract

The invention discloses an anti-pollution flashover coating with arc durability, which comprises the following components in parts by weight: 100 parts of hydroxyl-terminated polydimethylsiloxane, 10-25 parts of dimethyl silicone oil, 5-15 parts of a phosphorus flame retardant, 8-20 parts of white carbon black, 5-15 parts of modified mica powder, 15-30 parts of modified calcium carbonate, 10-20 parts of modified glass powder, 5-12 parts of aluminum hydroxide, 5-10 parts of 1, 3-butanediol, 5-10 parts of a flame retardant, 1-5 parts of an anti-aging agent, 1-5 parts of an anti-aging agent, and 1-5 parts of an anti-aging agent. The invention discloses a high-temperature-resistant coating which is prepared from the following components in parts by weight: 0.5-2 parts of 1, 2-bis (trimethoxysilyl) ethane, 5-10 parts of potassium titanate whiskers, 2-6 parts of color paste, 50-150 parts of a solvent, 3-10 parts of a cross-linking agent, 2-6 parts of a silane coupling agent and 1-5 parts of a catalyst. The invention also provides a preparation method of the anti-pollution flashover coating with arc durability. By introducing the modified mica powder, the modified glass powder and the modified calcium carbonate with specific particle sizes and reasonable gradation, the proportion of the filler in the base rubber is ensured, so that the modified mica powder, the modified glass powder and the modified calcium carbonate form a compact and firm ceramic high-temperature-resistant and arc-resistant layer after encountering high temperature of an arc; and the purpose of improving the arc durability is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings for power transmission and transformation equipment in electric power systems, and in particular relates to an anti-pollution flashover coating with arc durability and a preparation method thereof. Background Art

[0002] Under adverse weather conditions (such as fog, dew, drizzle, etc.), flashover will occur along the wet surface of the insulator, causing a flashover accident in the power system. Flashover threatens the safe and stable operation of the power system. In mild cases, it affects local power supply, and in severe cases, it affects the power grid and even causes the entire power grid to break. The impact of flashover on the power supply system has caused huge losses to the national economy.

[0003] Room Temperature Vulcanized Silicone Rubber (RTV) is abbreviated as RTV anti-pollution flashover coating. It prevents pollution flashover accidents through its excellent hydrophobicity. Since 2000, it has been rapidly developed and widely used in the domestic power transmission and transformation field as a new technology and new material with its outstanding characteristics such as long-lasting and maintenance-free.

[0004] The current anti-pollution flashover coating is mainly composed of a mixture of silicone rubber, fillers and vulcanizers. Its resistance to leakage tracking and electrical erosion is relatively low, generally AC 1A2.5 level. Although some anti-pollution flashover coatings can be 1A4.5 level, when the voltage level of the transmission network to which it is applied is below 1000kV, it cannot meet the application requirements of the DC ultra-high voltage transmission network above 1000kV under harsh conditions. In addition, the fillers used are mostly aluminum hydroxide, which is used to improve the resistance to leakage tracking and electrical erosion of the coating. Due to its good insulation and flame retardant properties and low price, it has become the most commonly used filler in anti-pollution flashover coatings. However, the addition of a large amount of aluminum hydroxide will greatly affect the mechanical properties and surface hydrophobicity of the anti-pollution flashover coating film after curing, and the bound water released by aluminum hydroxide under high-temperature arc erosion will make the coating surface rougher to a certain extent, thereby affecting its service life. Therefore, on the basis of improving the resistance to leakage tracking and electrical erosion of anti-pollution flashover coatings, how to ensure its mechanical properties at the same time has become an urgent problem to be solved.

[0005] For example, the anti-pollution flashover coating suitable for coating live equipment prepared in patent CN101717607A uses decabromodiphenyl ether as an arc-resistant agent, and the resistance to leakage tracking can reach 1A4.5 level; on the one hand, decabromodiphenyl ether is a halogen-containing substance and is not environmentally friendly; on the other hand, the product of decabromodiphenyl ether after high-temperature decomposition by electric arc is no longer arc-resistant, so the durability against arc is poor.

[0006] In addition, patent publication number CN102585506A discloses a silicone rubber with excellent arc resistance, which uses a mixed filling of boron nitride and aluminum hydroxide, which greatly reduces the electrolytic corrosion loss compared with silicone rubber using aluminum hydroxide alone. However, the use of boron nitride is relatively expensive, which increases the cost of materials. On the other hand, boron nitride has extremely high hardness and wear resistance, which leads to a decrease in its mechanical properties and is prone to cracking during use. Summary of the invention

[0007] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the main purpose of the present invention is to provide a high-temperature arc resistant anti-pollution flashover coating with low cost and excellent mechanical properties and arc durability. The present invention also provides a preparation method of the high-temperature arc resistant anti-pollution flashover coating.

[0008] The objective of the present invention is achieved through the following technical solutions:

[0009] In the first aspect, an anti-pollution flashover coating with arc durability comprises the following components in parts by weight: 100 parts of terminal hydroxyl polydimethylsiloxane, 10-25 parts of dimethyl silicone oil, 5-15 parts of phosphorus flame retardant, 8-20 parts of white carbon black, 5-15 parts of modified mica powder, 15-30 parts of modified calcium carbonate, 10-20 parts of modified glass powder, 5-12 parts of aluminum hydroxide, 1,2-bis(trimethoxysilyl)ethane, 5-10 parts of potassium titanate whiskers, 2-6 parts of color paste, 50-150 parts of solvent, 3-10 parts of cross-linking agent, 2-6 parts of silane coupling agent, and 1-5 parts of catalyst.

[0010] In some specific embodiments, the terminal hydroxyl polydimethylsiloxane includes low-viscosity terminal hydroxyl polydimethylsiloxane and high-viscosity terminal hydroxyl polydimethylsiloxane, the viscosity of the low-viscosity terminal hydroxyl polydimethylsiloxane at 25°C is 2000-6000 mPa·s, the viscosity of the high-viscosity terminal hydroxyl polydimethylsiloxane at 25°C is 8000-12000 mPa·s, and the mass ratio of the low-viscosity terminal hydroxyl polydimethylsiloxane to the high-viscosity terminal hydroxyl polydimethylsiloxane is (1-3):1.

[0011] In some specific embodiments, the white carbon black has a specific surface area of ​​150-250m 2 / g of hydrophobic white carbon black.

[0012] In certain specific embodiments, the crosslinking agent is methyltributylidene oxime silane, the silane coupling agent is KH-550, and the catalyst is selected from one of dibutyltin dilaurate and stannous octoate.

[0013] In some specific embodiments, the dimethyl silicone oil has a viscosity of 100-200 mPa·s at 25°C.

[0014] In some specific embodiments, the mesh size of the mica powder is 40-60 μm, the mesh size of the calcium carbonate is 100-150 μm, and the mesh size of the glass powder is 5-15 μm.

[0015] In some specific embodiments, the aluminum hydroxide has a particle size of 5-30 μm, and the potassium titanate whisker has a length of 20-30 μm and a diameter of 1 μm.

[0016] In some specific embodiments, the solvent is No. 120 solvent gasoline.

[0017] In some specific embodiments, the phosphorus-based flame retardant consists of 2-ethylhexyl diphenyl phosphate and hexafluorocyclotriphosphazene, and the mass ratio of the 2-ethylhexyl diphenyl phosphate to the hexafluorocyclotriphosphazene is 1:2-6.

[0018] In a second aspect, a method for preparing an anti-pollution flashover coating having arc durability comprises the following steps:

[0019] 1) According to the formula requirements, mica powder, calcium carbonate, or glass powder is mixed with 1,2-bis(trimethoxysilyl)ethane in a ratio of 100:(1-3), the temperature is raised to 80-100° C. and stirred for 30-40 minutes to obtain modified mica powder, modified calcium carbonate and modified glass powder;

[0020] 2) Add the formulated amount of terminal hydroxyl polydimethylsiloxane, dimethyl silicone oil and phosphorus flame retardant into a kneader, stir evenly at a speed of 40-60 rpm, then add white carbon black, modified mica powder, modified calcium carbonate, modified glass powder, aluminum hydroxide, potassium titanate whisker and color paste in sequence, and adjust the speed to 80-120 rpm; after heating to 80-120° C., turn on the vacuum to remove bubbles and small molecules, and maintain the speed at 80-120 rpm for 1.5-2 hours to mix the materials in the kneader evenly;

[0021] 3) After the material obtained in step 2) is cooled to room temperature, it is transferred to a three-roll mill for grinding until the grinding fineness of the material is less than 30 μm, and then transferred to a first stirring kettle, and then a solvent is added, and after preliminary dispersion at a speed of 40-80 rpm, it is transferred to an emulsifier and repeatedly emulsified 3-5 times to mix evenly to obtain a semi-finished product material;

[0022] 4) The semi-finished product obtained in step 3) is transferred to a second stirring kettle, and then the silane coupling agent, cross-linking agent and catalyst are added in the formula amount, and after being stirred evenly at a speed of 40-150 rpm, the material is discharged to obtain an anti-pollution flashover coating with arc durability.

[0023] Compared with the prior art, the present invention has at least the following advantages:

[0024] 1) The anti-pollution flashover coating with arc durability provided by the present invention ensures the proportion of the aforementioned fillers in the base glue by introducing modified mica powder, modified glass powder and modified calcium carbonate with specific particle size and reasonable grading, so that the modified mica powder, modified glass powder and modified calcium carbonate form a dense and strong ceramic high temperature resistant and arc resistant layer after encountering the high temperature of the arc, thereby achieving the purpose of improving the arc durability.

[0025] 2) The anti-pollution flashover coating with arc durability provided by the present invention improves the proportion of mica powder, glass powder and calcium carbonate in the base glue by modifying mica powder, glass powder and calcium carbonate with 1,2-bis(trimethoxysilyl)ethane having 6 functional groups; and the surfaces of the modified mica powder, glass powder and calcium carbonate contain hydroxyl groups, which can form a tight chemical bond with the active groups in the terminal hydroxyl polydimethylsiloxane. The ceramic layer formed after being subjected to the high temperature of the arc is evenly distributed in the entire coating, which is more uniform and dense, arc-resistant, and the electro-corrosion performance is greatly improved.

[0026] 3) The anti-pollution flashover coating with arc durability provided by the present invention is prepared by adding potassium titanate whiskers into the system. The potassium titanate whiskers are fibrous potassium titanate whiskers with the characteristics of high mechanical strength, heat insulation, heat resistance and corrosion resistance. The addition of potassium titanate whiskers further "connects" the system in series, thereby improving the mechanical properties of the coating and further improving its arc resistance.

[0027] 4) The present invention adopts modified mica powder, modified glass powder and modified calcium carbonate with specific particle size and reasonable grading, combined with potassium titanate whiskers and other prior art features, so that the prepared anti-pollution flashover coating has the properties of resistance to leakage tracking and electrical erosion, and ensures that it also has flame retardant properties, mechanical properties and the like that meet the requirements of relevant industry standards. DETAILED DESCRIPTION

[0028] The present invention will be further described in detail below in conjunction with specific embodiments. The following embodiments are merely illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0029] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values ​​with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values ​​listed herein include the endpoints of the range, and all integers and fractions within the range.

[0030] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.

[0031] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.

[0032] The invention provides an anti-pollution flashover coating with arc durability, which comprises the following components in parts by weight: 100 parts of terminal hydroxyl polydimethylsiloxane, 10-25 parts of dimethyl silicone oil, 5-15 parts of phosphorus flame retardant, 8-20 parts of white carbon black, 5-15 parts of modified mica powder, 15-30 parts of modified calcium carbonate, 10-20 parts of modified glass powder, 5-12 parts of aluminum hydroxide, 1,2-bis(trimethoxysilyl)ethane, 5-10 parts of potassium titanate whisker, 2-6 parts of color paste, 50-150 parts of solvent, 3-10 parts of cross-linking agent, 2-6 parts of coupling agent and 1-5 parts of catalyst.

[0033] The terminal hydroxyl polydimethylsiloxane comprises a low-viscosity terminal hydroxyl polydimethylsiloxane and a high-viscosity terminal hydroxyl polydimethylsiloxane, wherein the viscosity of the low-viscosity terminal hydroxyl polydimethylsiloxane at 25°C is 2000-6000 mPa·s, the viscosity of the high-viscosity terminal hydroxyl polydimethylsiloxane at 25°C is 8000-12000 mPa·s, and the mass ratio of the low-viscosity terminal hydroxyl polydimethylsiloxane to the high-viscosity terminal hydroxyl polydimethylsiloxane is (1-3):1; the white carbon black has a specific surface area of ​​150-250 m 2 / g of hydrophobic white carbon black; wherein the crosslinking agent is methyl tributylidene oxime silane, the coupling agent is KH-550, and the catalyst is selected from one of dibutyltin dilaurate and stannous octoate; wherein the viscosity of the dimethyl silicone oil at 25°C is 100-200mPa·s; wherein the mesh size of the mica powder is 40-60μm, the mesh size of the calcium carbonate is 100-150μm, and the mesh size of the glass powder is 5-15μm; wherein the hydroxide The particle size of aluminum oxide is 5-30 μm, the length of the potassium titanate whisker is 20-30 μm, and the diameter is 0.2-0.6 μm, wherein the solvent is No. 120 solvent gasoline; wherein the phosphorus-based flame retardant is composed of 2-ethylhexyl diphenyl phosphate and hexafluorocyclotriphosphazene, and the mass ratio of the 2-ethylhexyl diphenyl phosphate and hexafluorocyclotriphosphazene is 1:2-6 (it should also be noted that the particle size or mesh size of each filler is the average particle size or average mesh size).

[0034] Example 1

[0035] The method for preparing the anti-pollution flashover coating with arc durability provided by the present invention comprises the following steps:

[0036] 1) According to the formula requirements, mica powder, calcium carbonate, or glass powder is mixed with 1,2-bis(trimethoxysilyl)ethane in a ratio of 100:1, the temperature is raised to 80° C. and stirred for 40 minutes to obtain modified mica powder, modified calcium carbonate and modified glass powder;

[0037] 2) Add 100 parts of terminal hydroxyl polydimethylsiloxane, 10 parts of dimethyl silicone oil and 5 parts of phosphorus flame retardant into a kneader, stir evenly at a speed of 40 rpm, then add 8 parts of white carbon black, 10 parts of modified mica powder, 15 parts of modified calcium carbonate, 20 parts of modified glass powder, 5 parts of aluminum hydroxide, 5 parts of potassium titanate whiskers and 3 parts of color paste in sequence, and adjust the speed to 80 rpm; after heating to 80° C., turn on the vacuum to remove bubbles and small molecules, and maintain the speed at 120 rpm for 1.5 hours to mix the materials in the kneader evenly;

[0038] 3) After the material obtained in step 2) is cooled to room temperature, it is transferred to a three-roll mill for grinding until the grinding fineness of the material is less than 30 μm, and then transferred to a first stirring kettle, and then 60 parts of solvent are added, and after preliminary dispersion at a speed of 40 rpm, it is transferred to an emulsifier and repeatedly emulsified 4 times to mix evenly to obtain a semi-finished product material;

[0039] 4) The semi-finished product obtained in step 3) is transferred to a second stirring kettle, and then 3 parts of a silane coupling agent, 6 parts of a cross-linking agent and 4 parts of a catalyst are added, and after stirring evenly at a speed of 100 rpm, the material is discharged to obtain an anti-pollution flashover coating with arc durability.

[0040] The terminal hydroxyl polydimethylsiloxane comprises a low-viscosity terminal hydroxyl polydimethylsiloxane and a high-viscosity terminal hydroxyl polydimethylsiloxane, wherein the viscosity of the low-viscosity terminal hydroxyl polydimethylsiloxane at 25°C is 2000 mPa·s, the viscosity of the high-viscosity terminal hydroxyl polydimethylsiloxane at 25°C is 8000 mPa·s, and the mass ratio of the low-viscosity terminal hydroxyl polydimethylsiloxane to the high-viscosity terminal hydroxyl polydimethylsiloxane is 3:1; the white carbon black has a specific surface area of ​​250 m 2 / g of hydrophobic white carbon black; wherein the viscosity of the dimethyl silicone oil at 25°C is 100mPa·s; wherein the mesh size of the mica powder is 40μm, the mesh size of the calcium carbonate is 100μm, and the mesh size of the glass powder is 10μm; wherein the particle size of the aluminum hydroxide is 25μm, the length of the potassium titanate whisker is 25μm, and the diameter is 1μm, wherein the phosphorus-based flame retardant is composed of 2-ethylhexyl diphenyl phosphate and hexafluorocyclotriphosphazene in a mass ratio of 1:4.

[0041] Example 2

[0042] The method for preparing the anti-pollution flashover coating with arc durability provided by the present invention comprises the following steps:

[0043] 1) According to the formula requirements, mica powder, calcium carbonate, or glass powder is mixed with 1,2-bis(trimethoxysilyl)ethane in a ratio of 100:2, the temperature is raised to 90° C. and stirred for 35 minutes to obtain modified mica powder, modified calcium carbonate and modified glass powder;

[0044] 2) Add 100 parts of terminal hydroxyl polydimethylsiloxane, 20 parts of dimethyl silicone oil and 10 parts of phosphorus flame retardant into a kneader, stir evenly at a speed of 40 rpm, then add 15 parts of white carbon black, 10 parts of modified mica powder, 25 parts of modified calcium carbonate, 15 parts of modified glass powder, 8 parts of aluminum hydroxide, 8 parts of potassium titanate whiskers and 4 parts of color paste in sequence, and adjust the speed to 80 rpm; after heating to 120° C., turn on the vacuum to remove bubbles and small molecules, and maintain the speed at 120 rpm for 2 hours to mix the materials in the kneader evenly;

[0045] 3) After the material obtained in step 2) is cooled to room temperature, it is transferred to a three-roll mill for grinding until the grinding fineness of the material is less than 30 μm, and then transferred to a first stirring kettle, and then 120 parts of solvent are added, and after preliminary dispersion at a speed of 60 rpm, it is transferred to an emulsifier and repeatedly emulsified 4 times to mix evenly to obtain a semi-finished product material;

[0046] 4) The semi-finished product obtained in step 3) is transferred to a second stirring kettle, and then 4 parts of a silane coupling agent, 6 parts of a cross-linking agent and 3 parts of a catalyst are added, and after stirring evenly at a speed of 100 rpm, the material is discharged to obtain an anti-pollution flashover coating with arc durability.

[0047] The terminal hydroxyl polydimethylsiloxane comprises a low-viscosity terminal hydroxyl polydimethylsiloxane and a high-viscosity terminal hydroxyl polydimethylsiloxane, wherein the viscosity of the low-viscosity terminal hydroxyl polydimethylsiloxane at 25°C is 3000 mPa·s, the viscosity of the high-viscosity terminal hydroxyl polydimethylsiloxane at 25°C is 10000 mPa·s, and the mass ratio of the low-viscosity terminal hydroxyl polydimethylsiloxane to the high-viscosity terminal hydroxyl polydimethylsiloxane is 2:1; the white carbon black has a specific surface area of ​​200 m 2 / g of hydrophobic white carbon black; wherein the viscosity of the dimethyl silicone oil at 25°C is 150mPa·s; wherein the mesh size of the mica powder is 50μm, the mesh size of the calcium carbonate is 120μm, and the mesh size of the glass powder is 10μm; wherein the particle size of the aluminum hydroxide is 20μm, the length of the potassium titanate whisker is 25μm, and the diameter is 1μm, wherein the phosphorus-based flame retardant is composed of 2-ethylhexyl diphenyl phosphate and hexafluorocyclotriphosphazene in a mass ratio of 1:4.

[0048] Example 3

[0049] The method for preparing the anti-pollution flashover coating with arc durability provided by the present invention comprises the following steps:

[0050] 1) According to the formula requirements, mica powder, calcium carbonate, or glass powder is mixed with 1,2-bis(trimethoxysilyl)ethane in a ratio of 100:3, the temperature is raised to 100° C. and stirred for 40 minutes to obtain modified mica powder, modified calcium carbonate and modified glass powder;

[0051] 2) Add 100 parts of terminal hydroxyl polydimethylsiloxane, 25 parts of dimethyl silicone oil and 15 parts of phosphorus flame retardant into a kneader, stir evenly at a speed of 60 rpm, then add 18 parts of white carbon black, 15 parts of modified mica powder, 25 parts of modified calcium carbonate, 20 parts of modified glass powder, 10 parts of aluminum hydroxide, 8 parts of potassium titanate whisker and 4 parts of color paste in sequence, and adjust the speed to 120 rpm; after heating to 120° C., turn on the vacuum to remove bubbles and small molecules, and maintain the speed at 120 rpm for 1.5 hours to mix the materials in the kneader evenly;

[0052] 3) After the material obtained in step 2) is cooled to room temperature, it is transferred to a three-roll mill for grinding until the grinding fineness of the material is less than 30 μm, and then transferred to a first stirring kettle, and then 150 parts of solvent are added, and after preliminary dispersion at a speed of 80 rpm, it is transferred to an emulsifier and repeatedly emulsified 4 times to mix evenly to obtain a semi-finished product material;

[0053] 4) The semi-finished product obtained in step 3) is transferred to a second stirring kettle, and then 6 parts of silane coupling agent, 6 parts of cross-linking agent and 4 parts of catalyst are added, and after stirring evenly at a speed of 100 rpm, the material is discharged to obtain an anti-pollution flashover coating with arc durability.

[0054] The terminal hydroxyl polydimethylsiloxane comprises a low-viscosity terminal hydroxyl polydimethylsiloxane and a high-viscosity terminal hydroxyl polydimethylsiloxane, wherein the viscosity of the low-viscosity terminal hydroxyl polydimethylsiloxane at 25°C is 2000 mPa·s, the viscosity of the high-viscosity terminal hydroxyl polydimethylsiloxane at 25°C is 12000 mPa·s, and the mass ratio of the low-viscosity terminal hydroxyl polydimethylsiloxane to the high-viscosity terminal hydroxyl polydimethylsiloxane is 3:1; the white carbon black has a specific surface area of ​​150 m 2 / g of hydrophobic white carbon black; wherein the viscosity of the dimethyl silicone oil at 25°C is 100-200mPa·s; wherein the mesh size of the mica powder is 50μm, the mesh size of the calcium carbonate is 150μm, and the mesh size of the glass powder is 15μm; wherein the particle size of the aluminum hydroxide is 25μm, the length of the potassium titanate whisker is 15μm, and the diameter is 1μm, wherein the phosphorus-based flame retardant is composed of 2-ethylhexyl diphenyl phosphate and hexafluorocyclotriphosphazene in a mass ratio of 1:5.

[0055] This application takes Example 2 as an example, and performs a performance test on the prepared anti-pollution flashover coating with arc durability according to the detection method in the power industry standard DL / 627-2018; in addition, this application also refers to GB / T 6553-2014 (Test method for assessing tracking and erosion resistance of electrical insulating materials used under severe conditions) to test the prepared anti-pollution flashover coating for its tracking and erosion resistance under high voltage environment, wherein the test sample is 50×120mm and 6mm thick; the test sample is tested for 6h at a test voltage of 2.5kV-4.5kV for tracking and erosion resistance tests, and the specific results are shown in Table 1:

[0056] Table 1 Performance test results of the anti-pollution flashover coating prepared in Example 2 of the present invention

[0057] Test items Standard requirements Example 2 Appearance ○ ○ Dry time ≤4h 50min Curing time ≤24h 4h Hydrophobicity HC1-HC2 HC1 Volume resistivity <![CDATA[≥1.0×10 12 ]]> <![CDATA[2.9×10 14 ]]> Resistant to tracking and erosion ≥TMA2.5 Level 4.5 Tear strength ≥7.0KN / m 8.1KN / m Mechanical breaking strength ≥3.0MPa 4.2MPa Elongation at break ≥200% 380% Flammability ≥FV-1 FV-0 Adhesion ≥ Grade 1 Level 0 Impulse breakdown voltage ≥18kv / mm 27.8kv / mm Tracking and corrosion resistance under severe conditions —— 1A3.5

[0058] Note: ○Good △Fair ×Poor

[0059] As can be seen from Table 1, the anti-pollution flashover coating with arc durability and the preparation method thereof provided by the present invention have a faster curing speed, and have excellent volume resistivity, breakdown voltage, tensile strength, etc., tear elongation, resistance to leakage tracking, resistance to high-temperature electrical corrosion, etc., and at the same time, under harsh conditions, it also has excellent resistance to electrical tracking and corrosion, meets the relevant requirements for the roof insulation of electric locomotives, and greatly improves the construction efficiency while ensuring performance.

[0060] Comparative Example 1

[0061] The components and proportions of the anti-pollution flashover coating with arc durability provided in this comparative example are basically the same as those in Example 2, except that the mica powder, calcium carbonate and glass powder are not modified; the process steps are the same as those in Example 2.

[0062] The performance of the anti-pollution flashover coating prepared in Comparative Example 1 was tested according to the detection method in the power industry standard DL / 627-2018. The specific results are shown in Table 2:

[0063] Table 2 Performance test results of the anti-pollution flashover coating prepared in Example 2 of the present invention / Comparative Example 1

[0064] Test items Standard requirements Example 2 Comparative Example 1 Appearance ○ ○ ○ Dry time ≤4h 50min 50min Curing time ≤24h 4h 4h Hydrophobicity HC1-HC2 HC1 HC1 Volume resistivity <![CDATA[≥1.0×10 12 ]]> <![CDATA[2.9×10 14 ]]> <![CDATA[2.8×10 13 ]]> Resistant to tracking and erosion ≥TMA2.5 Level 4.5 Level 2.5 Tear strength ≥7.0KN / m 8.1KN / m 5.1KN / m Mechanical tear strength ≥3.0MPa 4.2MPa 3.0MPa Elongation at break ≥200% 380% 290% Flammability ≥FV-1 FV-0 FV-0 Adhesion ≥ Grade 1 Level 0 Level 0 Impulse breakdown voltage ≥18kv / mm 27.8kv / mm 23.1kv / mm Tracking and corrosion resistance under severe conditions —— 1A3.5 1A2.5

[0065] Note: ○Good △Fair ×Poor

[0066] As can be seen from Table 2, since mica powder, calcium carbonate and glass powder were not modified in Comparative Example 1, several fillers were physically dispersed in the system after curing and no chemical bonds occurred, resulting in the density of the cured system being not as good as that of the modified system in Example 2, and the mechanical, electrical and high temperature resistance properties all showed a significant decline.

[0067] Comparative Example 2

[0068] The components and proportions of the anti-pollution flashover coating with arc durability provided in this comparative example are basically the same as those in Example 2, except that the mica powder, calcium carbonate and glass powder are modified by using vinyltrimethoxysilane; the process steps are the same as those in Example 2.

[0069] The performance of the anti-pollution flashover coating prepared in Comparative Example 2 was tested according to the detection method in the power industry standard DL / 627-2018. The specific results are shown in Table 3:

[0070] Table 3 Performance test results of the anti-pollution flashover coating prepared in Example 2 of the present invention / Comparative Example 2

[0071]

[0072]

[0073] Note: ○Good △Fair ×Poor

[0074] As can be seen from Table 3, in Comparative Example 2, commonly used vinyltrimethoxysilane is used to modify mica powder, calcium carbonate and glass powder, so that the filler and the main resin can be chemically bonded, the density is further improved, and the mechanical properties and electrical corrosion resistance are improved. However, the 1,2-bis(trimethoxysilyl)ethane used in Example 2 has more active reaction groups than vinyltrimethoxysilane, and has less steric hindrance and is easier to combine with the filler to form a dense system structure. After the modification, a better bonding effect is achieved and the mechanical properties are better.

[0075] Comparative Example 3

[0076] The anti-pollution flashover coating with arc durability provided in this comparative example has components and proportions that are basically the same as those in Example 2, except that potassium titanate whiskers are not added; and the process steps are the same as those in Example 2.

[0077] The performance of the anti-pollution flashover coating prepared in Comparative Example 3 was tested according to the detection method in the power industry standard DL / 627-2018. The specific results are shown in Table 4:

[0078] Table 4 Performance test results of the anti-pollution flashover coating prepared in Example 2 / Comparative Example 3 of the present invention

[0079] Test items Standard requirements Example 2 Comparative Example 3 Appearance ○ ○ ○ Dry time ≤4h 50min 50min Curing time ≤24h 4h 4h Hydrophobicity HC1-HC2 HC1 HC1 Volume resistivity <![CDATA[≥1.0×10 12 ]]> <![CDATA[2.9×10 14 ]]> <![CDATA[1.2×10 14 ]]> Resistant to tracking and erosion ≥TMA2.5 Level 4.5 Level 3.5 Tear strength ≥7.0KN / m 8.1KN / m 6.1KN / m Mechanical tear strength ≥3.0MPa 4.2MPa 3.0MPa Elongation at break ≥200% 380% 300% Flammability ≥FV-1 FV-0 FV-0 Adhesion ≥ Grade 1 Level 0 Level 0 Impulse breakdown voltage ≥18kv / mm 27.8kv / mm 26.7kv / mm Tracking and corrosion resistance under severe conditions —— 1A3.5 1A2.5

[0080] Note: ○Good △Fair ×Poor

[0081] As can be seen from Table 4, the absence of potassium titanate whiskers in Comparative Example 3 resulted in a significant decrease in tear strength, mechanical tear strength and tear elongation, and a decrease in the relative tracking index; this is mainly because potassium titanate whiskers, as a high-performance reinforcing fiber, can further "connect the system in series", effectively improving the mechanical properties of the coating and the relative tracking index.

[0082] Comparative Example 4

[0083] The components and proportions of the anti-pollution flashover coating with arc durability provided in this comparative example are basically the same as those in Example 2, except that the particle sizes of the modified mica powder, modified calcium carbonate and modified glass powder used are all 30-50μm; and the process steps are the same as those in Example 2.

[0084] The performance of the anti-pollution flashover coating prepared in Comparative Example 4 was tested according to the detection method in the power industry standard DL / 627-2018. The specific results are shown in Table 5:

[0085] Table 5 Performance test results of the anti-pollution flashover coating prepared in Example 2 / Comparative Example 4 of the present invention

[0086] Test items Standard requirements Example 2 Comparative Example 4 Appearance ○ ○ ○ Dry time ≤4h 50min 50min Curing time ≤24h 4h 4h Hydrophobicity HC1-HC2 HC1 HC1 Volume resistivity <![CDATA[≥1.0×10 12 ]]> <![CDATA[2.9×10 14 ]]> <![CDATA[1.5×10 14 ]]> Resistant to tracking and erosion ≥TMA2.5 Level 4.5 Level 2.5 Tear strength ≥7.0KN / m 8.1KN / m 6.8KN / m Mechanical tear strength ≥3.0MPa 4.2MPa 3.8MPa Elongation at break ≥200% 380% 330% Flammability ≥FV-1 FV-0 FV-0 Adhesion ≥ Grade 1 Level 0 Level 0 Impulse breakdown voltage ≥18kv / mm 27.8kv / mm 26.7kv / mm Tracking and corrosion resistance under severe conditions —— 1A3.5 1A2.5

[0087] Note: ○Good △Fair ×Poor

[0088] As can be seen from Table 5, the mechanical properties and anti-corrosion properties of Comparative Example 4 using three fillers with the same particle size are somewhat reduced compared with those of Example 2 using different particle sizes. The use of fillers with different particle sizes can form a denser stacking, improve the overall strength of the system, and provide strong technical support for the improvement of mechanical and anti-corrosion properties.

[0089] Comparative Example 5

[0090] The anti-pollution flashover coating with arc durability provided in this comparative example has components and proportions that are basically the same as those of Example 2, except that only modified mica powder is added; its process steps are the same as those of Example 2.

[0091] The performance of the anti-pollution flashover coating prepared in Comparative Example 5 was tested according to the detection method in the power industry standard DL / 627-2018. The specific results are shown in Table 6:

[0092] Table 6 Performance test results of the anti-pollution flashover coating prepared in Example 2 of the present invention / Comparative Example 5

[0093] Test items Standard requirements Example 2 Comparative Example 5 Appearance ○ ○ ○ Dry time ≤4h 50min 50min Curing time ≤24h 4h 4h Hydrophobicity HC1-HC2 HC1 HC1 Volume resistivity <![CDATA[≥1.0×10 12 ]]> <![CDATA[2.9×10 14 ]]> <![CDATA[2.1×10 14 ]]> Resistant to tracking and erosion ≥TMA2.5 Level 4.5 Level 2.5 Tear strength ≥7.0KN / m 8.1KN / m 7.5KN / m Mechanical tear strength ≥3.0MPa 4.2MPa 3.3MPa Elongation at break ≥200% 380% 320% Flammability ≥FV-1 FV-0 FV-0 Adhesion ≥ Grade 1 Level 0 Level 0 Impulse breakdown voltage ≥18kv / mm 27.8kv / mm 26.7kv / mm Tracking and corrosion resistance under severe conditions —— 1A3.5 1A0

[0094] Note: ○Good △Fair ×Poor

[0095] As can be seen from Table 6, in Comparative Example 5, only modified mica powder is used as arc-resistant filler, and its anti-corrosion performance is significantly reduced. This is because the general mica powder has limited high temperature resistance (generally 600°C), so when it is under high pressure, the arc generates high temperature, which causes the composition or structure of the coating to change, resulting in poor arc durability of the coating, that is, poor resistance to tracking and erosion under high pressure test conditions. In Example 2, modified mica powder, modified calcium carbonate and modified glass powder can be further formed at high temperature. The ceramic structure has excellent high temperature resistance and can greatly improve the durability against arc corrosion high temperature.

[0096] Comparative Example 6

[0097] The anti-pollution flashover coating with arc durability provided in this comparative example has components and proportions that are basically the same as those in Example 2, except that only modified calcium carbonate is added; its process steps are the same as those in Example 2.

[0098] The performance of the anti-pollution flashover coating prepared in Comparative Example 6 was tested according to the detection method in the power industry standard DL / 627-2018. The specific results are shown in Table 7:

[0099] Table 7 Performance test results of the anti-pollution flashover coating prepared in Example 2 / Comparative Example 6 of the present invention

[0100]

[0101]

[0102] Note: ○Good △Fair ×Poor

[0103] As can be seen from Table 7, Comparative Example 6 uses only calcium carbonate as an arc-resistant filler, and its anti-corrosion performance has a significant decrease. This is because the high temperature resistance of general calcium carbonate is limited, generally around 500°C, so when it is under a high-voltage environment, the arc generates high temperature, which causes the composition or structure of the coating to change, resulting in poor arc durability of the coating, that is, poor resistance to tracking and erosion under high-voltage test conditions. While Example 2 uses modified mica powder, modified calcium carbonate and modified glass powder to further form a ceramic structure at high temperature. The ceramic structure has excellent high temperature resistance and can greatly improve resistance to high temperature of arc corrosion.

[0104] Comparative Example 7

[0105] The components and proportions of the anti-pollution flashover coating with arc durability provided in this comparative example are basically the same as those of Example 2, except that only modified glass powder is added; the process steps are the same as those of Example 2.

[0106] The performance of the anti-pollution flashover coating prepared in Comparative Example 7 was tested according to the detection method in the power industry standard DL / 627-2018. The specific results are shown in Table 8:

[0107] Table 8 Performance test results of the anti-pollution flashover coating prepared in Example 2 of the present invention / Comparative Example 7

[0108]

[0109]

[0110] Note: ○Good △Fair ×Poor

[0111] As can be seen from Table 8, Comparative Example 7 uses only glass powder as an arc-resistant filler, and its anti-corrosion performance has been significantly reduced. This is because the general glass powder has a high temperature resistance of about 800°C, so when it is under a high-voltage environment, the arc generates high temperature, which causes the composition or structure of the coating to change, resulting in poor arc durability of the coating, that is, poor resistance to tracking and erosion under high-voltage test conditions. While Example 2 uses mica powder, calcium carbonate and glass powder to further form a ceramic structure at high temperature. The ceramic structure has excellent high temperature resistance and can greatly improve resistance to high temperature of arc erosion.

[0112] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. An anti-pollution flashover coating with arc durability, It is characterized in that The invention comprises the following components in parts by weight: 100 parts of terminal hydroxyl polydimethylsiloxane, 10-25 parts of dimethyl silicone oil, 5-15 parts of phosphorus flame retardant, 8-20 parts of white carbon black, 5-15 parts of modified mica powder, 15-30 parts of modified calcium carbonate, 10-20 parts of modified glass powder, 5-12 parts of aluminum hydroxide, 0.5-2 parts of 1,2-bis(trimethoxysilyl)ethane, 5-10 parts of potassium titanate whisker, 2-6 parts of color paste, 50-150 parts of solvent, 3-10 parts of crosslinking agent, 2-6 parts of silane coupling agent and 1-5 parts of catalyst.

2. The anti-pollution flashover coating with arc durability according to claim 1, It is characterized in that The terminal hydroxyl polydimethylsiloxane comprises a low-viscosity terminal hydroxyl polydimethylsiloxane and a high-viscosity terminal hydroxyl polydimethylsiloxane, wherein the viscosity of the low-viscosity terminal hydroxyl polydimethylsiloxane at 25°C is 2000-6000 mPa·s, the viscosity of the high-viscosity terminal hydroxyl polydimethylsiloxane at 25°C is 8000-12000 mPa·s, and the mass ratio of the low-viscosity terminal hydroxyl polydimethylsiloxane to the high-viscosity terminal hydroxyl polydimethylsiloxane is (1-3):

1.

3. The anti-pollution flashover coating with arc durability according to claim 1, It is characterized in that The white carbon black has a specific surface area of ​​150-250m 2 / g of hydrophobic white carbon black.

4. The anti-pollution flashover coating with arc durability according to claim 1, It is characterized in that The cross-linking agent is methyl tributylidene oxime silane, the silane coupling agent is KH-550, and the catalyst is selected from one of dibutyltin dilaurate and stannous octoate.

5. The anti-pollution flashover coating with arc durability according to claim 4, It is characterized in that The viscosity of the dimethyl silicone oil at 25° C. is 100-200 mPa·s.

6. The anti-pollution flashover coating with arc durability according to claim 4, It is characterized in that The mesh size of the mica powder is 40-60 μm, the mesh size of the calcium carbonate is 100-150 μm, and the mesh size of the glass powder is 5-15 μm.

7. The anti-pollution flashover coating with arc durability according to claim 4, It is characterized in that The particle size of the aluminum hydroxide is 5-30 μm, and the length of the potassium titanate whisker is 20-30 μm and the diameter is 1 μm.

8. The anti-pollution flashover coating with arc durability according to claim 4, It is characterized in that The solvent is No. 120 solvent gasoline.

9. The anti-pollution flashover coating with arc durability according to claim 4, It is characterized in that The phosphorus-based flame retardant consists of 2-ethylhexyl diphenyl phosphate and hexafluorocyclotriphosphazene, and the mass ratio of the 2-ethylhexyl diphenyl phosphate to the hexafluorocyclotriphosphazene is 1:2-6.

10. A method for preparing an anti-pollution flashover coating having arc durability, It is characterized in that The steps include: 1) According to the formula requirements, mica powder, calcium carbonate, or glass powder is mixed with 1,2-bis(trimethoxysilyl)ethane in a ratio of 100:(1-3), the temperature is raised to 80-100° C. and stirred for 30-40 minutes to obtain modified mica powder, modified calcium carbonate and modified glass powder; 2) Add the formulated amount of terminal hydroxyl polydimethylsiloxane, dimethyl silicone oil and phosphorus flame retardant into a kneader, stir evenly at a speed of 40-60rpm, then add white carbon black, modified mica powder, modified calcium carbonate, modified glass powder, aluminum hydroxide, potassium titanate whisker and color paste in sequence, and adjust the speed to 80-120rpm; after heating to 80-120°C, turn on the vacuum to remove bubbles and small molecules, and maintain the speed at 80-120rpm for 1.5-2h to mix the materials in the kneader evenly; 3) After the material obtained in step 2) is cooled to room temperature, it is transferred to a three-roll mill for grinding until the grinding fineness of the material is less than 30 μm, and then transferred to a first stirring kettle, and then a solvent is added, and after preliminary dispersion at a speed of 40-80 rpm, it is transferred to an emulsifier and repeatedly emulsified 3-5 times to mix evenly to obtain a semi-finished product material; 4) The semi-finished product obtained in step 3) is transferred to a second stirring kettle, and then the silane coupling agent, cross-linking agent and catalyst are added in the formula amount, and after being stirred evenly at a speed of 40-150 rpm, the material is discharged to obtain an anti-pollution flashover coating with arc durability.

Citation Information

Patent Citations

  • Anti-explosive splattering paint and preparation method thereof

    CN101942273A

  • Silicone sealant

    CN107936908A

  • Anti-freezing acid-resistant polymer cement waterproof coating and preparation method thereof

    CN110591479A

  • Single-component dealcoholized silicone sealant and preparation method thereof

    CN112662370A

  • Improved anti-pollution flashover coating and preparation method thereof

    CN113122130A

Cited By

  • Fluorocarbon nano insulating paint with high stability and preparation method thereof

    CN120758171A

  • Flame-retardant heat-conducting silica gel insulating paint and preparation method thereof

    CN122037777A

  • Flame-retardant heat-conducting silica gel insulating paint and preparation method thereof

    CN122037777B